Conflictos culturales en el manejo de cuencas hidrográficas en el Istmo Centroamericano - Mojica, Iván H. (Revista de Biología Tropical, 1976)
Productivity of natural ecosystems in watersheds in the Central American Isthmus is being seriously endangered by the disproportionate increase in population, which hampers an adequate development of water and agricultural resources. The logical consequences of the lack of planning in the use of these resources are rapid degradation of the soil and high levels of environmental pollution. Among the human activities which destroy the natural ecological balance are slash burning, overgrazing and farming on lands not suited for this purpose. These activities Corm part of the socioeconomic and cultural aspects of the region and are associated with systems of land occupancy and distribution, and with inefficient practices, such as tenant farming and share cropping. Recent apprehensions by nature-loving groups and the general public are pressing for more realistic conservation and legislative policies, and for the creation of more dynamic government agencies that would not only actively participate in the planning and utilization of natural resources, but also in the technical studies of watersheds that alter the socio-cultural aspects of the Central American region.